Optimal space-time transceiver design for selective wireless broadcast with channel state information. - Jianzhong Zhang (IEEE Transactions on wireless communications)
Selective broadcast schemes for point-to-multiple point transmission of identical information to several selected users are studied for a code-division multiple-access wireless system. The channel states for all selected users are assumed known at both the transmitter and the receivers. The goal is to minimize total transmit power while satisfying minimum received signal-to-noise ratio (SNR) requirements. Three designs, namely, time-only, space-time and space-only, are investigated. In the time-only design no spatial diversity is available, and we solve the optimal transmit signature code by developing iterative least distance programming (ILDP) and linear programming (LP) algorithms. In the space-time design, transmit antennas are exploited in addition to the temporal dimension, and we show the ILDP algorithm is still applicable. The LP algorithm can also be adapted with the integration of space-time block codes, which we term the space-time block coding LP (STC-LP) algorithm. In the space-only design, only the spatial dimension is available and we study the optimization of the transmit antenna weights to satisfy the users' SNR requirements. We show that the STC-LP algorithm applies in this case. We also propose an iterative spatial diagonalization algorithm to explore the unique structure of the space-only problem.